(untitled) (jornal of the libyan geographical society, 2009)
There is widespread dissatisfaction among African planners about the spatial distribution of the population and the degree of urban dominance in particular. This study documents the growing importance of national urban development strategies in African development plans and examines other factors involved in the adoption of these spatial development policies. This study found a weak relationship between urban hegemony and the adoption of spatial policy. Other factors, such as government stability and the level of national independence, show a stronger relationship with the adoption of rural service center policies, shopping towns, and urban systems policies in general.